Professional commitment, self-efficacy and ethical decision auditor - Dewi, Putu Purnama; Dwiyanti, Kadek Trisna (International research journal of management, IT and social sciences, 2018)
This study aims to test and obtain empirical evidence on the influence of professional commitment on ethical decisions and the influence of self efficacy in moderating the relationship between professional commitment and ethical decisions of auditors Public Accounting Firm (KAP) in Bali Province. Sources of data used are primary data with the type of data used is quantitative data, obtained through the dissemination and filling questionnaires by auditors KAP. Data analysis technique used is with approach of regression analysis of moderation or Moderated Regression Analyze (MRA). The results of this study indicate that professional commitment has a positive effect on ethical decision auditor, self efficacy auditor able to moderate the relationship between professional commitment and ethical decision auditor.